2014
DOI: 10.1177/1933719113488449
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of CD10 in the Development of Endometriosis Due to Its Inhibitory Effects on CD44-Dependent Cell Adhesion

Abstract: A reduced response to progesterone in the eutopic endometrium with endometriosis and in endometriotic tissues is considered to be the underlying factor for endometriosis. CD10 is known to be expressed by endometrial and endometriotic stromal cells and may be induced by progestins, although the function of CD10 is not fully revealed in endometrial or endometriotic tissues. In the current study, the expression of CD10 was significantly increased by treatment of the cells with progesterone, 17b-estradiol, and dib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Several research groups evaluated hyaluronic acid (HA) as a potential targeting ligand to the CD44 receptor, which was previously suggested to be overexpressed in endometriosis cells and human endometriotic lesions. [ 75,76 ] It was also revealed that CD44 expression in normal endometrium is detected only in the secretory but not in the proliferative phase, indicating hormonal regulation of this receptor. [ 77 ] Zhao et al.…”
Section: Accumulation Of Nanoparticles In Endometriosis Lesionsmentioning
confidence: 99%
“…Several research groups evaluated hyaluronic acid (HA) as a potential targeting ligand to the CD44 receptor, which was previously suggested to be overexpressed in endometriosis cells and human endometriotic lesions. [ 75,76 ] It was also revealed that CD44 expression in normal endometrium is detected only in the secretory but not in the proliferative phase, indicating hormonal regulation of this receptor. [ 77 ] Zhao et al.…”
Section: Accumulation Of Nanoparticles In Endometriosis Lesionsmentioning
confidence: 99%
“…17 CD44, which was identified as HA receptor, was found to be overexpressed in endometriotic cells. 18 Interestingly, there was no effect on binding characteristics of HA-treated endometrial cell to mesothelial cell, suggesting that endometrial cells might have a potential to bind to HA of surrounding tissue. 2 So, it is a powerful method to shield the positive charge of gene vectors with the targeting ligands (HA) in the guidance of the concept of receptor-mediated endocytosis, which was aimed at directing gene delivery to desired tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of CD44 in ectopic endometria suggests that CD44 might play a meaningful role in the pathogenesis of endometriosis, as described earlier. 18,25,26 The light micrographs and electron micrograph. Notes: (A) Light micrographs of endometrial lesions.…”
Section: The Endometrial Expression Of Cd44mentioning
confidence: 99%
“…It is generally accepted that the establishment and development of Ems require retrograde menstruation or endometrial fragments, which contain aberrantly activated of eutopic EScs. This is followed by the migration, invasion, implantation and proliferation of these EScs on the surface or inner part of pelvic tissues or organs, which occurs simultaneously with a controlled local inflammatory response and angiogenesis (44). Multiple studies have suggested that EScs in patients with Ems possess different properties compared with the EScs of healthy controls (45,46).…”
Section: Discussionmentioning
confidence: 99%